The Integration of Green Economy and Human Resource Behavior in Bridging the Discrepancy Gap Towards Sustainable Development - Mas Wigrantoro Roes Setiyadi; Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study highlights the importance of integrating green economy and human resource (HR) behavior in reducing the gap discrepancy between the current state and long-term goals within the context of sustainability. HR plays a crucial role in supporting the transition to a green economy through interdisciplinary skills, efficient cost control, and a deep understanding of sustainability concepts. The gap discrepancy analysis reveals that the success of the green economy relies not only on changes in business practices or natural resource management but also on changes in the behavior and skills of the involved HR. Therefore, enhancing relevant training and fostering interdisciplinary collaboration are key to bridging this gap. Improving HR capacity in technical skills and understanding social and global responsibility must be a primary focus, enabling HR to implement sustainability principles in social and economic policies. In this way, HR can serve as change agents, accelerating the application of a more sustainable green economy and supporting the achievement of sustainable development that benefits society as a whole.